Back Pain and Quality of Life After Surgical Treatment for Adolescent Idiopathic Scoliosis at 5-Year Follow-up: Comparison with Healthy Controls and Patients with Untreated Idiopathic Scoliosis. (21st August 2019) - Helenius, Linda; Diarbakerli, Elias; Grauers, Anna; Lastikka, Markus; Oksanen, Hanna; Pajulo, Olli; Löyttyniemi, Eliisa; Manner, Tuula; Gerdhem, Paul; Helenius, Ilkka
Abstract : Background: Posterior spinal fusion with pedicle screws is the gold-standard treatment for adolescent idiopathic scoliosis (AIS); however, it is unclear whether this procedure results in improved long-term back pain and health-related quality of life compared with patients not surgically treated for AIS. The aim of the present study was to evaluate back pain and quality of life in surgically managed patients with a minimum follow-up of 5 years compared with patients with untreated AIS and a healthy control group. Methods: Fifty-five consecutive adolescent patients who underwent posterior pedicle screw instrumentation for AIS by a single orthopaedic surgeon were prospectively enrolled. At a minimum of 5 years postoperatively, 49 patients completed Scoliosis Research Society (SRS)-24 questionnaires, and data on reoperation were collected. Pain and quality-of-life parameters were compared with those of 49 age and sex-matched patients with untreated AIS and 49 healthy controls. Results: The major curve averaged 53° preoperatively and 12° at 2 years postoperatively. One reoperation (pedicle screw removal) was needed because of a new neurological deficit (transient). The SRS-24 pain, function, and total scores improved significantly from preoperatively to 5 years postoperatively (all p ⩽ 0.016), with pain scores improving from 4.0 to 4.3 (p = 0.003). There was no association between pain scores and the preoperative major curve, instrumentation below L1, or postoperative rib hump. The surgical treatment group had significantly better pain, activity, and self-image domain scores at 5 years postoperatively compared with the untreated AIS group (all p ⩽ 0.014), and similar pain, self-image, and activity domain scores compared with the healthy control group; function scores were significantly lower in the healthy control group compared with the surgical treatment group (p < 0.001). Conclusions: Patients who underwent posterior spinal fusion with pedicle screws experienced improved back pain and health-related quality of life compared with patients with untreated AIS. Patients in the surgical treatment group had similar health-related quality of life to that of the healthy control group, except for function, which was significantly lower. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.